(untitled) (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY:To gain insight into the determinants of radiologists’ professional satisfaction in Switzerland. METHODS:Data from 254 members of the Swiss Society of Radiology (76% men) obtained in a questionnaire survey were analysed by logistic regression analysis using socio-demographic, person- and workplace-related factors as independent variables (determinants) and satisfaction at work as the outcome variable. RESULTS:In terms of person-related factors within a complex logistical regression model, radiologists with low occupational self-efficacy and especially those with low mental wellbeing were at elevated risk for low professional satisfaction, with the latter determinant being the strongest predictor in the whole model. Regarding work-related determinants, low career satisfaction and high workload increased the risk of low job satisfaction while working in a university hospital was a protection factor against low job satisfaction with private practice being the reference. A total of 42% of the respondents enjoyed their job more, and 19% enjoyed it less compared to five years previously, while 39% experienced no change. CONCLUSION:Despite high workload, time and economic pressure, the majority of radiologists were professionally satisfied at a high level, which had even increased within the last five years. However, to keep this level of job satisfaction, career possibilities, especially in private practices, have to be improved. Furthermore, the radiologists’ important contribution to the diagnostic and therapeutic process has to be recognised professionally as well as economically.